(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new classes of open and closed functions defined between bitopological spaces, called weakly θ(τ_1,τ_2)b-open functions and weakly θ(τ_1,τ_2)b-closed functions. Moreover, several characterizations and some properties concerning weakly θ(τ_1,τ_2)b-open functions and weakly θ(τ_1,τ_2)b-closed functions are established.